Effects of subprimal, quality grade, and aging on display color and sensory properties of ground beef patties - Highfill, Carrie (Kansas State University, 2012)
A factorial arrangement of treatments was used to evaluate the effects of two subprimal types (chuck roll and knuckle), two quality grades (Premium Choice and Select), and three vacuum storage aging times before processing (7, 21, and 42 d) on ground beef patty display color stability and sensory attributes. At the end of each aging time, four knuckles or two chuck rolls representing their respective quality grade categories were combined and ground to form a sample batch. After a final grind, patties were formed using a patty machine, packaged in overwrapped trays, and displayed in a coffin-type retail case under continuous fluorescent lighting. Ground beef patties from chuck roll and Premium Choice subprimals had brighter red visual color scores, less discoloration, and higher (P<0.05) L*, a*, b*, and chroma values than those from knuckle and Select subprimals, respectfully. With increased display time, patties became (P<0.05) darker red and more discolored and had decreased L*, a*, b*, a/b ratio, and chroma values and increased hue angle values. Ground beef patties from Select knuckle subprimals had greater (P<0.05) oxygen consumption rate (OCR) than those from Premium Choice chuck roll, Select chuck roll and Premium Choice knuckle subprimals. Patties from subprimals aged 42 d had a lower metmyoglobin reducing ability (MRA) than those from subprimals aged 7 and 21 d. Greater aging and display times had higher (P<0.05) aerobic and lactic acid plate counts. In addition, thiobarbituric acid reactive substances values increased (P<0.05) from 7 to 21 d of aging and from 0 to 24 h of display. Ground beef patties from Premium Choice subprimals had a higher MUFA:SFA ratio (P<0.05) than those from Select subprimals. All treatments had acceptable sensory panel results with minimal differences due to treatment. Lower (P<0.05) peak force values for slice shear force and Lee-Kramer were recorded for patties from chuck roll, Premium Choice, and 42 d aged subprimals than those from knuckle, Select, and 7 d aged subprimals, respectfully. Overall, Premium Choice chuck rolls aged for fewer days would result in the most color stability and extended display life.
Keywords: Ground beef; Display color; Sensory; Aging; Quality grade; Food Science (0359)